Constitutional Values and Constitutional Identity in National Constitutions - Tribl, Norbert (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
National constitutions are the basis of our constitutional systems. The question is, however, whether each European constitutional system is the same or whether, on the contrary, they are all unique. The answer is twofold. Of course we might have the same values, the same principles, but we have unique characteristics and we have our own values as well. Each constitutional system has its own specific characteristics, based on the history of the constitutional community and the constitutional system itself. Reactions to certain events in history have shaped the constitutional community and the identity of the constitutional state. On this basis, it is possible to identify specific features that are specific to a given constitutional system, i.e. elements of its identity. At the same time, the constitutional system carries certain social and constitutional values which also define the system itself. We call these constitutional values, which could be different state by state, nation by nation and which created the idea of unity in diversity in Europe.KEYWORDS: identity, European values, national values, constitutional values, constitutional identity, national identity, national constitution.